THE NOVEL “YALDO KECHASI” (“THE NIGHT OF YALDA”) AS AN EXAMPLE OF INTERTEXT - Xojamurodova Oydin Xojamurod qizi (International Journal of Literature and Language Studies, 2026)
The article analyses the novel “Yaldo kechasi” (2025) by Xayriddin Sulton from the standpoint of the theory of intertextuality. The work is examined as an example of intertext through its hypertextual link with Abdulla Qodiriy’s novel “Oʻtkan kunlar” (“Bygone Days”), the strategy of literary mystification (the found manuscript and false authorship), stylistic imitation, the incorporation of historical documents, letters and poetic texts into the fabric of the novel, and allusions and reminiscences. The study also elucidates the novel’s character system and its interpretation of historical events on the basis of the principle of intertextuality, and substantiates that intertextuality is the leading means in the transformation of historical truth into artistic reality.